Strain IMB-1, a Novel Bacterium for the Removal of Methyl Bromide in Fumigated Agricultural Soils - Connell Hancock, Tracy L. (American Society for Microbiology, 1998)
A facultatively methylotrophic bacterium, strain IMB-1, that has been isolated from agricultural soil grows on methyl bromide (MeBr), methyl iodide, methyl chloride, and methylated amines, as well as on glucose, pyruvate, or acetate. Phylogenetic analysis of its 16S rRNA gene sequence indicates that strain IMB-1 classes in the alpha subgroup of the class Proteobacteria and is closely related to members of the genus Rhizobium. The ability of strain IMB-1 to oxidize MeBr to CO(2) is constitutive in cells regardless of the growth substrate. Addition of cell suspensions of strain IMB-1 to soils greatly accelerates the oxidation of MeBr, as does pretreatment of soils with low concentrations of methyl iodide. These results suggest that soil treatment strategies can be devised whereby bacteria can effectively consume MeBr during field fumigations, which would diminish or eliminate the outward flux of MeBr to the atmosphere.